Disturbed Sleep Due to use Short-Form Video (SFV) on Social Media and Academic Achievement: The Mediating Role of Academic Burnout - Nguyen, Pham Thi Thao; Trang, Pham Thi Quynh; Trang, Dao Thu; Chuc, Bui Thi Thanh (VNU Journal of Science: Education Research; Vol 41 No 4DO - 10.25073/2588-1159/vnuer.4893, 2025)
Short-form video (SFV) platforms are very popular among students, but the immersive features of these software make them prone to excessive use and addiction. This study not only examined the impact of disturbed sleep due to short-form video (SFV) on social media on academic achievement but also explored the mediating roles of academic burnout in this linkage. Based on data collected from 520 students at Vietnamese universities, this research revealed that disturbed sleep resulting from SFV on social media negatively affected the academic achievement of Vietnamese students. Furthermore, the findings indicated that academic burnout mediates this relationship. This study contributes to the existing literature by providing evidence on the relationship between disturbed sleep due to SFV on social media, mental health, and the academic achievement of youths. As a result, valuable policy recommendations were discussed to enhance academic performance and address mental health issues associated with social media use among university students.